Acupuncture for Parkinson's disease-related constipation: current evidence and perspectives - Zhang, Jiale; Ge, Xiaolei; Zhang, Kaiqi; Qi, Yun; Ren, Shuo; Zhai, Xu (Frontiers in Neurology, 2023)
Parkinson's disease-related constipation (PDC) is commonly associated with impaired dopamine transmission and gastrointestinal dysfunction. Current pharmacological treatments have limited efficacy and potential side effects. Acupuncture has shown promise as an alternative or adjunct therapy by modulating the brain–gut axis, gastrointestinal hormones, and autonomic function. Preliminary randomized trials have shown that acupuncture significantly improves constipation symptoms, bowel movements, and comfort compared to sham or drug treatments and is well-tolerated. The mechanisms of action may involve regulating the gut microbiota and mucosal immunity to improve dysbiosis and gastrointestinal motility. However, more rigorous studies are required to optimize acupuncture protocols and determine long-term efficacy and safety. In summary, acupuncture shows promise as an adjunct therapy for PDC, but further research is needed to confirm its efficacy and safety.